The impact of macroeconomic variables and the volatility index (VIX) on the Indonesian Composite Index - Winarno, Dwi; Manurung, Adler Haymans; Sembel, Roy; Hardiyanti, Siti Epa (Management Science Research Journal, 2023)
This study investigates the relationship and influence between variables in the context of the Indonesian Composite Stock Price Index (IHSG). The Vector Error Correction Model (VECM) is estimated using a dataset with a complete sample size of 32 and a final sample size of 27. The results of the study show that the IHSG has a significant influence on its own movement in each period, indicating a self-reinforcing pattern. The VIX index shows a significant negative influence on changes in IHSG in the previous period, indicating the impact of market volatility on the IHSG. On the other hand, variables such as Gross Domestic Product (GDP), Inflation, and Bank Indonesia's Middle Exchange Rate (Middle Rate BI) do not show a significant influence on changes in IHSG in the previous period. Furthermore, the analysis of long-term influence indicates that changes in IHSG in the previous period have a significant negative influence on changes in IHSG in the current period, reflecting a tendency towards long-term equilibrium. The VIX index also shows a significant positive influence on changes in IHSG in the current period, indicating short-term volatility effects. However, GDP, Inflation, and Middle Rate BI do not have a significant influence on changes in IHSG in the current period